GOOD GOVERNANCE AFFECTING EFFECTIVENESS OF SCHOOLS ATTACHED TO THE OFFICE OF PROMARY EDUCATIONAL IN NAKHON RATCHASIMA PROVINCE - saenkla, pramote551 (Pathumthani University Academic Journal, 2020)
The purposes of this research were to study : 1) the level of good governance of school attached to the Office of Primary Education area in Nakhon Ratchasima province. 2) the level of school effectiveness of school attached to the Office of Primary Education Area in Nakhon Ratchasima province. and 3) the good governance affecting school effectiveness of Schools attached to the Office of Primary Education area in Nakhon Ratchasima province.The populations were 1,332 school administrators attached to the Office of Primary Education Service Area in Nakhon Ratchasima Province. The sample were 297 school administrators. The research instrument was questionnaire on the level of administrative behavior in accordance with good governance and the level of perception on the effectiveness of the school. Data were analyzed by using the computing programs and statistics used in data analysis were frequency distribution, percentage, mean, standard deviation and multiple regression. It was found from the study that : 1. The level of good governance of school attached to the Office of Primary Education area in Nakhon Ratchasima province overall, it was in the highest level. When considering each component, it was found that every component at the highest level. When ranked in order from highest to lowest, it was found that the components of good governance with the highest average values in the first 3 levels were morality, equity and transparency. The final ranking was accountability. 2. The level of school effectiveness of school attached to the Office of Primary Education Area in Nakhon Ratchasima province overall, it was in the high level. When considering each component, it was found that every component at a high level. When ranked in order from highest to lowest, it was found that the component of school effectiveness respectively Include learning organizations, students desirable characteristics and student achievement. 3. In overall, good governance affecting school effectiveness with statistical significance at .01 level, which can predicted on 61.10 percent. When separated in each component, found that Consensus Oriented, Accountability and Participation affecting school effectiveness with statistical significance at .01 level, which can predicted together on 62.80 percent. 4. The Consensus Oriented and Accountability components affecting student achievement with statistical significance at .01 level. The Accountability and Consensus Oriented components affecting student desirable characteristics with statistical significance at .01 level. The Consensus Oriented Participation and Equity components affecting learning organization with statistical significance at .05 level., were found.